[01/37] kbuild: refactor subdir-ym calculation
diff mbox series

Message ID 20200601055731.3006266-1-masahiroy@kernel.org
State New
Headers show
Series
  • [01/37] kbuild: refactor subdir-ym calculation
Related show

Commit Message

Masahiro Yamada June 1, 2020, 5:56 a.m. UTC
Remove the unneeded variables, __subdir-y and __subdir-m.

Signed-off-by: Masahiro Yamada <masahiroy@kernel.org>
---

 scripts/Makefile.lib | 13 ++++---------
 1 file changed, 4 insertions(+), 9 deletions(-)

Patch
diff mbox series

diff --git a/scripts/Makefile.lib b/scripts/Makefile.lib
index 0d931cc0df94..748e44d5a1e3 100644
--- a/scripts/Makefile.lib
+++ b/scripts/Makefile.lib
@@ -39,16 +39,14 @@  ifdef need-modorder
 modorder	:= $(patsubst %/,%/modules.order, $(filter %/, $(obj-y)) $(obj-m:.o=.ko))
 endif
 
+# Subdirectories we need to descend into
+subdir-ym := $(sort $(subdir-y) $(subdir-m) \
+			$(patsubst %/,%, $(filter %/, $(obj-y) $(obj-m))))
+
 # Handle objects in subdirs
 # ---------------------------------------------------------------------------
 # o if we encounter foo/ in $(obj-y), replace it by foo/built-in.a
-#   and add the directory to the list of dirs to descend into: $(subdir-y)
 # o if we encounter foo/ in $(obj-m), remove it from $(obj-m)
-#   and add the directory to the list of dirs to descend into: $(subdir-m)
-__subdir-y	:= $(patsubst %/,%,$(filter %/, $(obj-y)))
-subdir-y	+= $(__subdir-y)
-__subdir-m	:= $(patsubst %/,%,$(filter %/, $(obj-m)))
-subdir-m	+= $(__subdir-m)
 ifdef need-builtin
 obj-y		:= $(patsubst %/, %/built-in.a, $(obj-y))
 else
@@ -56,9 +54,6 @@  obj-y		:= $(filter-out %/, $(obj-y))
 endif
 obj-m		:= $(filter-out %/, $(obj-m))
 
-# Subdirectories we need to descend into
-subdir-ym	:= $(sort $(subdir-y) $(subdir-m))
-
 # If $(foo-objs), $(foo-y), $(foo-m), or $(foo-) exists, foo.o is a composite object
 multi-used-y := $(sort $(foreach m,$(obj-y), $(if $(strip $($(m:.o=-objs)) $($(m:.o=-y)) $($(m:.o=-))), $(m))))
 multi-used-m := $(sort $(foreach m,$(obj-m), $(if $(strip $($(m:.o=-objs)) $($(m:.o=-y)) $($(m:.o=-m)) $($(m:.o=-))), $(m))))